Examples of analogies and generalizations in synthetic geometry - Agut, Ioana E.; Agut, Calin M. (Teaching Mathematics and Computer Science, 2010)
Teaching tools and different methods of generalizations and analogies are often used at different levels of education. Starting with primary grades, the students can be guided through simple aspects of collateral development of their studies. In middle school, high school and especially in entry-level courses in higher education, the extension of logical tools are possible and indicated.In this article, the authors present an example of generalization and then of building the analogy in 3-D space for a given synthetic geometric problem in 2-D.The idea can be followed, extended and developed further by teachers and students as well.